Dinamična analiza klimatizacijskega sistema s toplotno črpalko - Balen, Igor (Strojniški vestnik, 2000)
In this paper a dynamic operation analysis of a low-velocity central air-conditioning system with a heat pump in terms of the changing operating conditions during the year is performed. For this purpose an original hour-by-hour simulation model of the system has been developed. The model consists of two integrated parts:calculation of the heat loss or heat gain to the space and determination of the heating and cooling load imposed on the air-conditioning system. The hourly and monthly energy use results for the air-conditioning system with heat pump, also in comparison with standard central air-conditioning system, are presented in graphical form. Flexibility of the developed simulation model provides the possibility to analyze and compare different air-conditioning systems, including different energy-recovery systems.
Keywords: sistemi klimatizacijski; črpalke toplotne; analize dinamične; porabe energije; dinamična analiza; klimatizacija; toplotna črpalka